Ionotropes Induced Symmetrical Peripheral Gangrene: A Case Report: Gangrene - .O, Naushad; .S, Kaur; .M, Bashir (International Journal of Innovative Research in Medical Science, 2018)
Symmetrical peripheral gangrene is characterised by presence of distal ischemic changes in two or more extremities without the vessel obstruction[1]. It is a rare but serious complication in patients of septic shock receiving ionotropes[2] which may lead to limb amputation.